Spesifikasi Job Description Meeting Planner dalam Kegiatan MICE pada PT Hariyono Tour and Travel Cabang Malang - Panca Oktawirani (Diploma Travel Business, Faculty of Social and Political Science, Jember University, 2019)
Abstract MICE is growing industry. Due to global demands, MICE events to be one of the economic driving and creation or employment. MICE activities require personalqualifications with specific tasks. PT. Hariyono Tour and Travel as one business unit MICE event organizers in Malang prepare and plan particular job specifications. Human resources has an impact on the needs of competence in each field. One important area in organizing MICE activity is meeting planner who served as a planner, manage schedules, manage finances, help the committee correspondence with participants, helping locate the implementation, promotion, and marketing, the delegation, registration and request support staff, on site management, helped arrange transportation, accommodation, VIP treatment, and helps make the design, printing, and photographer. Keyword: Spesifikasi, Job Description, MICE